PROGRAM EDUKASI VIDEO PENCEGAHAN KEKERASAN VERBAL TERHADAP PENGETAHUAN ORANG TUA ANAK USIA SEKOLAH - Melyana Rahmawati; Dian Susmarini; Purnamasari, Meivita (SEKOLAH TINGGI ILMU KESEHATAN KESDAM IV DIPONEGORO, 2023)
There are still many cases of verbal abuse of children by parents. Verbal abuse can have serious impact. One of the causes of verbal abuse is the lack of parental knowledge. This study aims to determine the effect of educational videos on parents knowledge about preventing verbal abuse in children. The design of this study was a quasi-experimental pretest-post test with control group design. The sampling technique used stratified random sampling with a total of 46 respondents in Kalikesur Village. The instrument was adopted from Mysa (2016). Data analysis used Chi-square and Wilcoxon test. The mean age of respondents in the intervention group was 40.17 years old, while in the median in the control group was 35 years old. The majority of respondents in this study were women, elementary school, had two or less children, married, and income below the Banyumas UMK. The results of the study there was no difference in the pretest level of parental knowledge about preventing verbal abuse in children between the two groups (p=0.131) but there was a difference in the posttest (p=0.022). There is a difference between the pretest and posttest levels of parental knowledge in the intervention group (p=0.000), but there was no difference in the control group (p=0.133). There is an effect of educational videos on parents knowledge about preventing verbal abuse in children.